Habitat‐specific impacts of climate change in the Mata Atlântica biodiversity hotspot. Issue 12 (2nd September 2019) - Esser, Luíz Fernando; Neves, Danilo M.; Jarenkow, João André
Abstract: Aim: Elucidate the potential impacts of climate changes on the distribution and conservation of the multiple habitats of the Mata Atlântica biodiversity hotspot, which are often treated as a unique entity in ecological studies. Location: The whole extension of the South American Atlantic Forest Domain plus forest intrusions into the neighbouring Cerrado and Pampa Domains, which comprises rain forest ('core' habitat) and five environmentally marginal habitats, namely high elevation/latitude forest, rock outcrop habitats, riverine forest, semideciduous forest and restinga woodlands. Time period: Current (2000) and future scenarios (2050 and 2070). Major taxa studied: Tree species. Methods: We modelled the responses of 282 diagnostic tree species, using multiple algorithms and distinct scenarios of climate change (828, 234 projections). Results: Potential loss of suitable environment summed 50.4% in semideciduous forest, 58.6% in riverine forest and 66% in rock outcrop habitats. Predictions for rain forest (12.2%), restinga woodlands (7.6%) and high elevation/latitude forest (5.2%) showed that overall loss of suitable environment will be relatively less severe for these habitats. Habitats that are confined to narrow edaphic conditions, namely rock outcrop habitats and riverine forest, are less studied and will likely suffer the greatest loss of biodiversity because their species are more dispersal limited. Main conclusions: Because these habitats occupy distinct environmental conditions, lumping them in ecological analyses might lead to erroneous interpretations in studies aiming to evaluate the impacts of global change in the Mata Atlântica biodiversity hotspot. This reinforces the importance of our approach and urges for conservation strategies that account for habitat heterogeneity in the Mata Atlântica and other species‐rich environments.